Analisis Kesehatan Bank Jatim Di Era Pandemi - Siti Lailatul Fitriyah; Isyrohil Muyassaroh (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
This research aimed to test whether there were differences in the level of banking soundness before and during Covid-19 at PT. Bank Pembangunan Daerah  Jawa Timur Tbk. (East Java Regional Development Bank or Bank Jatim) during 2016–2021. This research is quantitative descriptive research without testing the hypothesis. This study measures the soundness of banks using the RGEC method (risk profile, good corporate governance, earnings, and capital). The results of this study provide empirical evidence that during the Covid-19 pandemic, namely 2020-2021 and 2019-2020 (before Covid-19) the performance of the East Java Regional Development Bank had a very healthy level of health in terms of the ratio of LDR, LAR, CAR, NIM, while the CR ratio before the pandemic at a healthy level rose to very healthy and in 2021 decreased again with a healthy predicate, while the NPL ratio did not change to a good predicate, while the IRR ratio decreased to unhealthy. The ROA ratio also decreased from very healthy to be healthy, while GCG increased in 2021 to be good from those in 2019 and 2020 which were quite good.